Comparison of thrombus burden in patients with COVID-19 presenting with ST-segment elevation myocardial infarction across the three waves of outbreak in the United Kingdom. (3rd October 2022) - Teoh, Z; Rathod, K; Tyrlis, A; Choudry, F; Comer, K; Guttmann, O; Jain, A; Wragg, A; Archbold, A; Baumbach, A; Mathur, A; Jones, D
Abstract: Background: It has been previously reported during the first COVID outbreak that patients presenting with ST-Segment Elevation Myocardial Infarction (STEMI) and concurrent COVID-19 infection have increased thrombus burden and poorer outcomes [1]. Subsequently, there have been multiple further waves of the pandemic with the emergence of at least two new COVID-19 variants and the emergence of vaccinations. To-date, there have been no reports comparing the outcomes of COVID-19-positive STEMI patients across all waves of the pandemic. Purpose: The purpose of this study was to compare the baseline demographic, procedural and angiographic characteristics alongside the clinical outcomes of patients presenting with STEMI and concurrent COVID-19 infection across the COVID-19 pandemic in the UK. Methods: This was a single-centre, observational study of 1250 consecutive patients admitted with confirmed STEMI treated with primary percutaneous coronary intervention (PCI) at Barts Heart Centre between 01/03/2020 and 10/03/2022. COVID +ve patients were split into 3 groups based upon the time course of the pandemic (Wave 1: March 2020-June 2020, Wave 2: Sept 2020-March 2021, Wave 3: October 2021-March 2022). Comparison was made between waves and with a control group of COVID-ve patients treated during the same timeframe. Results: A total of 135 COVID +ive patients with STEMI (1st Wave: 39 patients, 2nd Wave: 60 patients, 3rd wave 35 pts) were included in the present analysis; and compared with 1115 COVID negative patients. Significant changes in the baseline characteristics, angiographic features and clinical outcomes of COVID +ive patients occurred over time. Early during the pandemic (Wave 1 2020), STEMI patients presenting with concurrent COVID-19 infection had high rates of cardiac arrest, evidence of increased thrombus burden (higher rates of multi-vessel thrombosis, stent thrombosis, higher modified thrombus grade higher use of GP IIb/IIIa inhibitors and thrombus aspiration, coagulability (more heparin for therapeutic ACT), bigger infarcts (lower myocardial blush grade and left ventricular function) and worse outcomes (mortality). However, by wave 3 (late 2021/2022), no differences existed in clinical characteristics, thrombus burden, infarct size or outcomes between COVID +ive patients and those without concurrent COVID-19 infection with significant differences compared to earlier COVID +ve patients. Poor outcomes later in the study period were predominantly in unvaccinated individuals. Conclusions: Significant changes have occurred in the clinical characteristics, angiographic features and outcomes of STEMI patients with COVID-19 infection treated by primary PCI during the course of the pandemic. Importantly it appears that angiographic features and outcomes of recent waves are no different to a non-COVID-19 population. Funding Acknowledgement: Type of funding sources: None.